2015
DOI: 10.1186/s12929-015-0154-y
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of mutant HSP27 causes axonal neuropathy in mice

Abstract: BackgroundMutations in heat shock 27 kDa protein 1 (HSP27 or HSPB1) cause distal hereditary motor neuropathy (dHMN) or Charcot-Marie-Tooth disease type 2 F (CMT2F) according to unknown factors. Mutant HSP27 proteins affect axonal transport by reducing acetylated tubulin.ResultsWe generated a transgenic mouse model overexpressing HSP27-S135F mutant protein driven by Cytomegalovirus (CMV) immediate early promoter. The mouse phenotype was similar to dHMN patients in that they exhibit motor neuropathy. To determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 25 publications
(26 reference statements)
4
26
0
Order By: Relevance
“…The recent generation of mouse models has provided novel insights concerning the relation between HSP mutations and CMT. Overexpression of either mutant HSPB1 S135F or HSPB1 P182L isoforms in the neuronal system leads to pronounced motor defects and reduced muscle strength, as monitored through behavioural tests (d'Ydewalle et al 2011;Lee et al 2015). While there is support for aberrant myelination in the latter study using the HSPB1 S135F model, a decrease in the levels of a-tubulin acetylation seems to be a common denominator of the observed pathology.…”
Section: Shsps In Motor Neuropathiesmentioning
confidence: 79%
“…The recent generation of mouse models has provided novel insights concerning the relation between HSP mutations and CMT. Overexpression of either mutant HSPB1 S135F or HSPB1 P182L isoforms in the neuronal system leads to pronounced motor defects and reduced muscle strength, as monitored through behavioural tests (d'Ydewalle et al 2011;Lee et al 2015). While there is support for aberrant myelination in the latter study using the HSPB1 S135F model, a decrease in the levels of a-tubulin acetylation seems to be a common denominator of the observed pathology.…”
Section: Shsps In Motor Neuropathiesmentioning
confidence: 79%
“…The c.404C>G mutation is located in the α‐crystallin domain (d'Ydewalle et al , ) . This domain is related to mitochondrial movement, which is important to maintain the integrity of cellular cytoskeleton transport (Lee et al , ) . The mutation may lead to loss of the cytoskeleton stabilizing role of HSPB1, a known pathogenic pathway associated with neuronal degeneration (Bonini et al , ) .…”
Section: Discussionmentioning
confidence: 99%
“…The mutation may lead to loss of the cytoskeleton stabilizing role of HSPB1, a known pathogenic pathway associated with neuronal degeneration (Bonini et al , ) . Overexpression of HSPB1‐S135F mutant protein reproduces motor neuropathy in mice (Lee et al , ) and leads to progressive degeneration of primary cultured mouse motor neurons associated with a disruption of neurofilament network (Zhai et al , ) .…”
Section: Discussionmentioning
confidence: 99%
“…Four mutant HSPB1 transgenic mouse models of dHMN have now been developed [8], [9], [10] and in 2011, d'Ydewalle et al. observed that treatment with a selective HDAC6 inhibitor successfully reversed the clinical phenotype of both S135F and P182L transgenic mice [8].…”
Section: Introductionmentioning
confidence: 99%